Recognition of Spirituality in Health Care: Personal and Universal Implications - Coulter, David L. (Journal of religion, disability & health, 2001)
Spirituality may be difficult to recognize among persons with significant intellectual and physical disabilities, yet it is present even when disability is so severe that consciousness is limited or absent. A clinical method is presented, based on the author's experience as a physician, that facilitates sharing of spirituality between caregivers and persons with disabilities. Caregivers must first accept their own spirituality and then seek to discover the spiritual essence of another person. Doing so provides insight into that which all persons have in common and leads (sometimes) to a religious experience of the ground of all spirituality. The method has universal implications across levels of ability and disability, across cultures and world religions, and across value systems involving science, human service and politics.